1985
DOI: 10.1001/jama.1985.03350360066020
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Hepatitis B Virus Transmission in the United States

Abstract: Among infants born to women in whom sera are positive for both the hepatitis B surface antigen and the e antigen, 85% to 90% are infected with hepatitis B virus and become chronic hepatitis B surface antigen carriers. In a study to assess the effectiveness of passive-active prophylaxis (hepatitis B immune globulin and hepatitis B vaccine) of such infants, we screened 18,842 pregnant Asian-American women: 8.7% were positive for hepatitis B surface antigen and 3.0% were also positive for hepatitis B e antigen. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Intrauterine MTCT of HBV is reported to occur in 10 to 16% of pregnancies and probably accounts for the small percentage of infants who do not respond to immunoprophylaxis treatment for HBV at birth. 4042 Intrauterine transplacental transmission due to leakage of maternal blood can occur during threatened abortion. 43,44 The risk of transmission of HBV from amniocentesis is low; in one study, the rate of MTCT did not significantly differ between women with HBV who underwent amniocentesis from those who did not undergo amniocentesis (9 vs 11%).…”
Section: Hepatitis B In Pregnancymentioning
confidence: 99%
“…Intrauterine MTCT of HBV is reported to occur in 10 to 16% of pregnancies and probably accounts for the small percentage of infants who do not respond to immunoprophylaxis treatment for HBV at birth. 4042 Intrauterine transplacental transmission due to leakage of maternal blood can occur during threatened abortion. 43,44 The risk of transmission of HBV from amniocentesis is low; in one study, the rate of MTCT did not significantly differ between women with HBV who underwent amniocentesis from those who did not undergo amniocentesis (9 vs 11%).…”
Section: Hepatitis B In Pregnancymentioning
confidence: 99%
“…It has been reported that immunoprophylaxis with both HBIG and hepatitis B vaccine could increase the efficacy of preventing perinatal HBV transmission to 85% to 95% and provide long-term protection 72,73. HBIG in indicated for postexposure prophylaxis after needle stick injury or percutaneous exposure.…”
Section: Preventionmentioning
confidence: 99%
“…Vertical transmission of HBV from hepatitis B surface antigen (HBsAg)-positive and hepatitis B e antigen (HBeAg)-positive pregnancies to infants remains the predominant mode of CHB infection, with up to 90% of infants from these pregnant women becoming chronically infected with HBV without immunoprophylaxis 14 , which may be partially due to the active replication and HBeAg positivity of women during their reproductive years 5, 6 . Programs combining postnatal active and passive immunoprophylaxis and universal vaccination have successfully reduced the transmission rates of HBV from > 90% to about 10% 3, 7, 8 ; however, there are still about 8%-30% of newborns that fail active HBV immunoprophylaxis (particularly those born to pregnant women with high serum HBV-DNA levels of > 2 × 10 5 –10 7 IU/mL 813 ), mainly due to a further increase in the global prevalence of CHB.…”
Section: Introductionmentioning
confidence: 99%